Philippines 1: Bringing Civil Society Into Capacity Development - Illo, Jearrne Frances I. (Archīum Ateneo, 2024)
The present assessment of technical cooperation (TC) in the Philippines takes a broad reading of the term capacity development. It looks at capacity as the ability to achieve several aims, including analysing and setting goals, and identifying the tasks and functions to reach these goals. Capacity also includes the ability to establish effective processes and mechanisms for participation and accountability, and to institute norms and values, rules and incentive structures to improve performance or realize a goal. This study looks into the “whose capacity” issue, and recognizes that these capacities can be vested within individuals, groups, and institutions - all contributing to capacity at the national level. Finally, this study also looks at the “for what” issue, interpreting capacity development as either a means or an end, as improvement of abilities to perform tasks or functions, as well as creating an environment that aids the development of “national goal-seeking capacity” (UNDP/UNICEF 1999).